Kepastian Hukum dan Keadilan Prosedural Studi Kriminologi Hukum terhadap Risiko Salah Putusan dalam KUHP Baru - Valentri Marlita Radja (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
Legal certainty and procedural justice constitute fundamental prerequisites in a modern criminal justice system to ensure that every process of punishment is conducted lawfully, fairly, and in full respect of human rights. However, the practice of criminal justice in Indonesia still demonstrates the risk of miscarriages of justice, including wrongful arrest, misapplication of legal provisions, and wrongful conviction, which potentially undermine the legitimacy of the legal system. The reform of national criminal law through the new Criminal Code (Law Number 1 of 2023) introduces a new paradigm emphasizing the principles of legality, proportionality, individualization of punishment, and the humanization of sentencing. Normatively, this reform is expected to strengthen legal certainty while simultaneously reinforcing procedural justice within the criminal justice process. This research aims to analyze: (1) the regulation of legal certainty and procedural justice under the new Criminal Code; (2) the factors within the criminal justice system that potentially give rise to wrongful convictions; (3) the criminological legal perspective on the occurrence of miscarriages of justice; and (4) the formulation of ideal legal policies to reinforce due process of law within the framework of the new Criminal Code. This study employs normative legal research with statutory, conceptual, and analytical approaches, supported by library research on primary, secondary, and tertiary legal materials. The findings indicate that the new Criminal Code has normatively strengthened legal certainty through a more systematic formulation of offenses, limitations on criminalization, and a clearer affirmation of the principle of legality and the protection of citizens’ rights. Nevertheless, the risk of wrongful conviction remains due to procedural weaknesses, such as suboptimal standards of proof, unequal access to legal assistance, the dominance of law enforcement authorities during the investigation stage, and limited corrective mechanisms for judicial errors. From the perspective of legal criminology, these conditions are understood as procedural and structural issues embedded in the design of the criminal justice system rather than merely individual mistakes of law enforcement officials. This study concludes that strengthening substantive norms in the new Criminal Code must be accompanied by the reformulation of procedural policies that emphasize stricter standards of proof, effective guarantees of legal assistance, accountable oversight mechanisms, and harmonization with criminal procedural law. Such efforts are essential to ensure that legal certainty and procedural justice are not merely declarative principles but are effectively implemented to prevent wrongful convictions and to reinforce the integrity of Indonesia’s criminal justice system.